Pengembangan Strategi Pemasaran pada Sentra UMKM Telur Asin Melalui Digital Marketing di Desa Jenggot Kecamatan Krembung - Wanda Silvialatus Sholikha; Wahyu Eko Pujianto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research aims to develop an effective marketing strategy for a salted egg Micro, Small, and Medium Enterprise (MSME) center in Jenggot Village, Krembung District. The problems faced by these MSMEs involve limited market access and the lack of utilization of digital marketing to increase the visibility of their products. The research methods used were market situation analysis, identification of target consumers, and implementation of digital marketing strategies. The research involved interviews with MSME owners, consumer surveys, and analysis of related market data. The results showed that the adoption of digital marketing strategies significantly increased the product exposure of salted egg MSMEs. Through the utilization of social media, websites, and e-commerce platforms, the MSMEs managed to reach a wider market and increase their product sales.